"Evaluación de briquetas como biocombustible s{olido a partir de residuos que generan los procesos agroindustriales en el sector El Empalme" - Macias Vera, Josselin Mercedes (2017)
The briquette is a solid biofuel, which is obtained by compaction or densification of waste, its composition is 100% natural, since they contain no binders, additives or other substance that can damage boilers and heating installations, its content is 100% waste from agro-industrial processes where the component that allows them to remain compact is lignin, a natural substance in wood that acts as a natural binder. The present work aims at the preparation and physical and chemical characterization of the briquette to be used as solid biofuel, in order to give greater added value to the Agroindustrial residues such as: rice husks, dust, cinder, and sawdust. A completely randomized block design was applied with an AxBxC factorial arrangement consisting of 12 treatments and 2 replicates corresponding to 24 treatments. The factors of study were: Factor A (type of mixture), factor B (briquette form) and factor C (briquette size). Tukey significance tests (p <0.05) were used to establish the differences between the levels, using the statistical program StatGraphics and Infostat. For the compaction process, molds of 10 and 15 cm square and cylindrical shapes were designed and manufactured, which ensured the solidity of the material when the mold was removed. Physical and chemical analyzes were performed on briquettes. After comparison with several authors it was determined that the best treatment was a_2 b_1 c_0 = T11 prepared with 4% rice husk, powder 14%, 10% cocoa, sawdust 12% square shape with a size of 10 cm , which presented the following characteristics: 4.35% ash, 11% moisture, calorific value 5268.20 Kcal / kg, density 1 g / cm3 and a compaction force of 6 , 51 PSI; being the outstanding treatment with the desired characteristics in a briquette, it was carried out tests of temperature and time of combustion, where it reached a range of (127-240) ºC in a time of 30 minutes to be fully calcined. Key words: Heat power, biomass, compaction, energy, combustion.